Performance Streaks in Elite Beach Volleyball - Does Failure in One Sideout Affect Attacking in the Next? - Link, Daniel; Wenninger, Sebastian (Frontiers in Psychology, 2019)
This study explores the influence of sideout failure on performance in the next sideout in beach volleyball. The sample comprises 965 elite matches in the FIVB World Series 2012-2016 and in the Olympic Games 2012/2016 including 28,974 sideout sequences (12,755 for men and 16,219 for women). A sideout sequence consists of two sideouts by the same player during the same set in a timeframe of four rallies. The first sideout in this sequence is referred as the previous sideout and the second sideout as the next sideout. After misses, 2-tests indicate a significantly higher technique change rate (from spike to shot or vice versa) in the next sideouts both for men (+32.7%) and women (+40.4%) compared to the next sideouts after hits. After shot misses, the share of shots in next sideouts was -12.9% lower for men and -8.3% lower for women compared to next sideouts after shot hits. After spike misses, the share of shots in next sideouts by female players was +5.5% significantly higher and shot hit rate was -6.5% lower compared to the next sideouts after spike hits. These findings support the belief that tactical decisions and performance in top-level beach volleyball are influenced by failure in previous sideouts. They might support coaches and players when analysing matches and developing game strategies.